The multidimensionality of business risk: A managerial perspective implications for its classification, interpretation & management - BAGRI, Prakash (Institutional Knowledge at Singapore Management University, 2019)
Business risk has been a critical area of managerial attention and the topic of extensive academic research. Despite the intense focus, there is little convergence around its understanding and limited insights on how managers deal with it. Extant literature provides an ex post model of business risk, focusing on the behavioural context of risk-taking driving a linear expression of risk action. We conducted in-depth interviews of 16 C-suite executives to find that managers (1) view business risk as a multi-dimensional construct involving different facets of risk, (2) emphasize the importance of people across these facets, (3) differ in their prioritization and interpretations of particular risk facets which together form their risk perceptions and (4) their perceptions influence their risk management action. Integrating findings from fieldwork with extant theory, we propose a conceptual model towards an ex ante understanding of business risk. Our model links individual, firm and industry-level variables to managerial prioritization and interpretation of business risk, and we use it to develop distinct research hypotheses. We carried out a second-stage quantitative survey of 182 managers from manufacturing, services and technology businesses. The results demonstrate (1) significant correlation between firm & industry-level variables and managerial perceptions of market-facing risks, (2) contradictions between managerial perceptions of different risk facets, particularly people risk, (3) paradoxical relationship between managerial experience and risk perceptions and (4) possible blind-spots in managerial perceptions of risk. Our research emphasizes the need to deal with business risk in a structured manner and to broaden organizational cognition whilst planning risk management efforts. Our study has implications for both managers and academics. We develop the risk management landscape as a systematic approach for dealing with risk and leveraging it for business advantage. Finally, we discuss limitations of our study, and consequent directions for future research.